Studi Analisis Terhadap Urgensi dan Implementasi Undang-Undang Nomor 8 Tahun 2010 Tentang Tindak Pidana Pencucian Uang - Ilham Ramadhan; Mia Puspita Sari; Nedi Aprizal; Tyo Qhoirun Nisa; Dimas Dwi Arso (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study is entitled Study Analisys of the Urgency and Implementation of the Law Number 8 of 2010 on Prevention and Punishment of Money Laundering. The development of the financial sector in Indonesia continues to progress, but the legal process has not followed the guidelines set by the Indonesian Financial Law and Regulations on Unlawful Money Transfer. Indonesia has enacted several laws to address this problem, including Financial and Material Law Number 8 of 2010, which aims to maintain economic stability and the integrity of the financial system, promote social harmony, economic growth, and government reform. The Indonesian government has implemented various measures to eradicate money laundering, including bilateral and multilateral forums, the concept of double crime, and the implementation of the